On Witold Lutosławski’s Artistic Self-Awareness. A Survey of Very Recent Research - Skowron Zbigniew (Musicology Today, 2016)
This paper presents the results of the most recent research concerning Witold Lutosławski’s artistic self-awareness, based on critical source editions of Lutosławski’s writings (publ. 2007–08). In the first part I discuss the edition of the composer’s ‘official’ writings contained in the collection Lutosławski on Music. These writings provide us with knowledge of the key elements of Lutosławski’s compositional technique and aesthetic principles, his attitude towards new music, and also to various problems of contemporary music culture in Poland and abroad. The second part of the article concerns Lutosławski’s notes contained in what is known as the Notebook of Ideas. Written in a characteristically personal tone, they illustrate the transformation of the composer’s artistic self-awareness that took place in the late 1950s and the early 1960s, when Lutosławski’s individual musical language was taking shape. The Notebook of Ideas sheds light, amongst other things, on the circumstances of composing Jeux vénitiens – the first work that puts into practice Lutosławski’s vision of twelve-tone harmony and controlled aleatorism.